Structure and Potential Scheme Reaction of a New Benzo[h]quinoline Derivative - BOUCHOUL, ABDELKADER; BENATHMANE, MUSTAPHA; BENBOUDIAF, ALI; BOUAOUD, SALAH; OUAHAB, LAHCENE; DJEBBAR, K.EZZINE (Asian Journal of Chemistry, 2010)
A new product namely, 2-methyl-3-ethyl methanoate benzo[h]quinoline was synthetized from an arylenamine using Vilsmeier reagent. The product was identified by classical and usual spectroscopic techniques as well as X-ray structure determination and a detailed potential scheme reaction way was proposed.